Fungus-mediated biotransformation of amorphous silica in rice husk to nanocrystalline silica - Bansal, Vipul; Ahmad, Absar; Sastry, Murali (Journal of American Chemical Society, 2006)
Rice husk is a cheap agro-based waste material, which harbors a substantial amount of silica in the form of amorphous hydrated silica grains. However, there have been no attempts at harnessing the enormous amount of amorphous silica present in rice husk and its room-temperature biotransformation into crystalline silica nanoparticles. In this study, we address this issue and describe how naturally deposited amorphous biosilica in rice husk can be bioleached and simultaneously biotransformed into high value crystalline silica nanoparticles. We show here that the fungus Fusarium oxysporum rapidly biotransforms the naturally occurring amorphous plant biosilica into crystalline silica and leach out silica extracellularly at room temperature in the form of 2-6 nm quasi-spherical, highly crystalline silica nanoparticles capped by stabilizing proteins; that the nanoparticles are released into solution is an advantage of this process with significant application and commercial potential. Calcination of the silica nanoparticles leads to loss of occluded protein and to an apparently porous structure often of cubic morphology. The room-temperature synthesis of oxide nanomaterials using microorganisms starting from potential cheap agro-industrial waste materials is an exciting possibility and could lead to an energy-conserving and economically viable green approach toward the large-scale synthesis of oxide nanomaterials.